Perlindungan Hukum terhadap Tenaga Kerja yang Terkena Pemutusan Hubungan Kerja (PHK) Akibat Force Majeure Saat Pandemi Covid 19 - thalib, sabrina; Adyuanas, Affan; Tri Hartana, Alan (IAI Nasional Laa Roiba Bogor, 2024)
The COVID-19 pandemic has had far-reaching impacts on the world in various aspects, including the economy. In Indonesia, the business ecosystem is one of the aspects that have been significantly affected by the pandemic. This has led many companies to implement mass layoffs (Pemutusan Hubungan Kerja or PHK) for employees who have been retrenched due to force majeure reasons. The purpose of this research is to understand the legal protection given to employees who have been retrenched, focusing on the Labor Law, specifically the UU No. 13 Year 2003 on Employment. Additionally, it aims to examine the role of the government in supporting the fulfillment of employees' rights and obligations during and after the COVID-19 pandemic, using a legal normative approach and a case study of the ruling No. 59/Pdt.Sus-PHI/2020/PN Gto.